Synthesis and pharmacological screening of certain N-arylformamidino-N'-subsituted-thiosemicarbazone Hydrochlorides as potential antithyroid agents - Tiwari U.K.; Srivastava P.K.; Verma V.K. (My University, 2025)
[No abstract available]